The construction and validation of an instrument for the assessment of graduates of undergraduate nursing courses - Maria Aparecida Vieira; Conceição Vieira da Silva Ohara; Edvane Birelo Lopes de Domenico (Universidade de São Paulo, 2016)
Abstract Objective: to construct an instrument for the assessment of graduates of undergraduate nursing courses and to validate this instrument through the consensus of specialists. Method: methodological study. In order to elaborate the instrument, documental analysis and a literature review were undertaken. Validation took place through use of the Delphi Conference, between September 2012 and September 2013, in which 36 specialists from Brazilian Nursing participated. In order to analyze reliability, the Cronbach alpha coefficient, the item/total correlation, and the Pearson correlation coefficient were calculated. Results: the instrument was constructed with the participation of specialist nurses representing all regions of Brazil, with experience in lecturing and research. The first Delphi round led to changes in the first instrument, which was restructured and submitted to another round, with a response rate of 94.44%. In the second round, the instrument was validated with a Cronbach alpha of 0.75. Conclusion: the final instrument possessed three dimensions related to the characterization of the graduate, insertion in the job market, and evaluation of the professional training process. This instrument may be used across the territory of Brazil as it is based on the curricular guidelines and contributes to the process of regulation of the quality of the undergraduate courses in Nursing.